The Spectrum of Vitamin D Deficiency: Description of a Family - Vierucci, Francesco; Del Pistoia, Marta; Randazzo, Emioli; Massart, Francesco; Federico, Giovanni (Experimental and Clinical Endocrinology & Diabetes, 2017)
Background Vitamin D deficiency represents a global health problem, affecting children and adolescents worldwide.Objects To confirm that vitamin D deficiency can present as a spectrum of clinical pictures.Methods We diagnosed nutritional rickets in a 10-month-old infant of Senegal origin with several risk factors for vitamin D deficiency. As many of these factors affected also his cohabitant relatives, we evaluate infant’s family members (mother and 4 brothers) looking for other vitamin D deficiency-related comorbidities.Results 3 brothers had asymptomatic vitamin D deficiency and 2 of them (9.8 and 13.4 years-old) showed secondary hyperparathyroidism. The fourth brother (11.3 years-old) had nutritional rickets. Their mother was affected by osteomalacia. None of them received vitamin D supplementation.Conclusion Vitamin D deficiency may present as a spectrum of clinical pictures, representing a continuum ranging from asymptomatic/subtle conditions to overt rickets/osteomalacia. Immigrant families are at high risk for vitamin D deficiency at every age. If a case of symptomatic vitamin D deficiency is recognized, then the evaluation of the all family members is recommended, as they can have the same and/or other risk factors for vitamin D deficiency.
Keywords: nutritional rickets; hypocalcemia; hyperparathyroidism; adolescence; osteomalacia